Beyond a diagnosis: The experience of depression among clinically‐referred adolescents. (30th August 2015) - Midgley, Nick; Parkinson, Sally; Holmes, Josh; Stapley, Emily; Eatough, Virginia; Target, Mary
Abstract: Policy‐makers have identified an urgent need to improve our ability to detect and diagnose depression in adolescents. This study aims to explore the lived experience of depression in clinically referred adolescents. 77 adolescents, aged between 11 and 17 with moderate to severe depression, were interviewed as part of a randomised controlled trial, using the Expectations of Therapy Interview . Data were analysed qualitatively using framework analysis, with a focus on how the adolescents spoke about their depression. The study identified five themes: 1) Misery, despair and tears; 2) Anger and violence towards self and others; 3) A bleak view of everything; 4) Isolation and cutting off from the world; and 5) The impact on education. Researchers and policy‐makers need to develop an understanding of depression grounded in the experiences of adolescents to improve detection and diagnosis of depression.